2019
DOI: 10.1002/lno.11372
|View full text |Cite
|
Sign up to set email alerts
|

Time‐series observations of photosynthetic oxygen production in the subtropical western North Pacific by an underwater profiling buoy system

Abstract: We conducted time-series observations in the northwestern part of the North Pacific subtropical gyre (30 N, 145 E) from July 2012 to March 2013 using a profiling buoy system equipped with a fast repetition rate fluorometer and dissolved oxygen (DO) sensor in order to understand vertical and temporal variations in gross oxygen production (GOP) by phytoplankton and its contribution to the oxygen cycle in the upper ocean. Under stratified conditions (July-November), daily GOP slightly exceeded 2 mmol O 2 m −3 d −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
5
4
0
Order By: Relevance
“…In region C, the surface Chl-a concentrations increased after the shallowing of the mixed layer and with sufficient light in summer (Figure 8h and 8i). These features are consistent with regional studies in the literature (e.g., Baldry et al, 2020;Fujiki et al, 2020;Mignot et al 2014;Sverdrup, 1953). The latitudinal dependence of the occurrence of the subsurface Chl-a maxima also pointed out in Cornec et al (2021).…”
Section: Discussionsupporting
confidence: 91%
“…In region C, the surface Chl-a concentrations increased after the shallowing of the mixed layer and with sufficient light in summer (Figure 8h and 8i). These features are consistent with regional studies in the literature (e.g., Baldry et al, 2020;Fujiki et al, 2020;Mignot et al 2014;Sverdrup, 1953). The latitudinal dependence of the occurrence of the subsurface Chl-a maxima also pointed out in Cornec et al (2021).…”
Section: Discussionsupporting
confidence: 91%
“…10h, i). These features are consistent with regional studies reported in the literature (e.g., Baldry et al, 2020;Fujiki et al, 2020;Mignot et al, 2014;Sverdrup, 1953). The latitudinal dependence of the subsurface Chl a maxima occurrence was also noted by Cornec et al (2021).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with an f ratio of 15 % reported at station ALOHA (23 • N 158 • W; Karl et al, 1996), considering a small but nonzero seasonal dissolved inorganic carbon drawdown reported in the subtropical surface layer (Yasunaka et al, 2013(Yasunaka et al, , 2021. It should be noted that oxygen production is not always associated with an increase in biomass at shallow depths in the subtropics (Fujiki et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with the f-ratio of 15% reported at station ALOHA (23°N 158°W; Karl et al, 1996), considering small but nonzero seasonal dissolved inorganic carbon drawdown reported in the subtropical surface layer (Yasunaka et al, 2013(Yasunaka et al, , 2021. However, it should be noted that oxygen production is sometimes not associated with biomass increase in shallow layers in the subtropics (Fujiki et al, 2020).…”
Section: Discussionsupporting
confidence: 88%